Liver enzyme and risk of vascular dementia: A univariable and multivariable Mendelian randomization of European descent - Jieyu Chen; Jianzhun Chen; Chunyu Liang; Chenxi Liu; Liu Jie; Bin Liu; Xinglong Yang (Neuroprotection)
Abstract Background Observational studies have indicated a link between liver enzymes and dementia, but the causal relationship remains uncertain. We conducted a two‐sample Mendelian randomization (MR) study to investigate potential causal links between liver function markers (alanine aminotransferase [ALT], aspartate aminotransferase [AST], alkaline phosphatase [ALP], and γ‐glutamyltransferase [GGT]) and various forms of dementia (all‐cause dementia, Alzheimer's disease [AD], vascular dementia [VaD], and frontotemporal dementia [FTD]). Methods Genome‐wide association study (GWAS) data of liver enzyme levels with 517 single nucleotide polymorphisms from 315,572 individuals of European descent were considered as exposures. Additional GWAS data on dementia from the FinnGen consortium and the UK Biobank were used as outcomes. The causal relationship was evaluated using univariable MR (UVMR) and multivariable MR (MVMR) methods. UVMR approaches such as inverse variance weighting (IVW), MR‐Egger, weighted median, simple mode, and weighted mode were used, with IVW as primary. MVMR techniques, such as extended versions of IVW, MR‐Egger, and Q‐minimization methods, were used to assess causal effects. The robustness of the MR analysis findings was verified through heterogeneity, horizontal pleiotropy, and leave‐one‐out analyses. Results MVMR analysis demonstrated that a genetically determined one standard deviation rise in blood GGT levels was associated with an increased risk of VaD (IVW: odds ratio = 1.007, 95% confidence interval = 1.002–1.011, p = 0.010). These findings remained consistent after adjusting for confounding variables in MVMR analysis. Sensitivity analyses further supported the causal relationship. However, no significant links were observed between ALT, AST, ALP, and all‐cause dementia, VaD, AD, or FTD. Conclusions Our study suggests clinical implications, demonstrating that high blood GGT concentrations are potential causal risk factors for VaD in European populations. Further research is needed to uncover the underlying biological mechanisms between GGT and VaD and validate the clinical relevance of early prevention and intervention strategies.